Isolation of locally-derived stem/progenitor cells from the peri-infarct area that do not migrate from the lateral ventricle after cortical stroke - Shimada, Issei S (2010)
BACKGROUND AND PURPOSE: Neurogenesis can arise from neural stem/progenitor cells of the subventricular zone (SVZ) after strokes involving both the cortex and striatum. However, it is controversial whether all types of stroke and strokes of different sizes activate neurogenesis from the SVZ niche. In contrast with cortical/striatal strokes, repair and remodeling after mild cortical strokes may involve to a greater extent local cortical stem/progenitor cells and cells from non-neurogenic niches. METHODS: We compared stem/progenitor cell responses after focal cortical strokes produced by distal Middle Cerebral Artery Occlusion (dMCAO) and cortical/striatal strokes produced by the intraluminal suture model. To label migrating neuroblasts from the SVZ, we injected DiI to the lateral ventricle after dMCAO. By immunohistochemistry, we characterized cells expressing stem/progenitor cell markers in the peri-infarct area. We isolated cortical stem/progenitor cells from the peri-infarct area following dMCAO and assayed their self-renewal and differentiation capacity. RESULTS: In contrast with cortical/striatal strokes, focal cortical strokes did not induce neuroblast migration from the SVZ to the infarct zone following dMCAO. By immunohistochemistry, we observed sub-populations of reactive astrocytes in the peri-infarct area that co-expressed radial glial cell markers such as Sox2, Nestin, and RC2. Neural spheres clonally-isolated from the peri-infarct area after dMCAO differentiated into neurons, astrocytes, oligodendrocytes, and smooth muscle cells. Notably, neural spheres isolated from the peri-infarct area also expressed RC2 prior to differentiation. CONCLUSIONS: Mild cortical strokes that do not penetrate the striatum activate local cortical stem/progenitor cells but do not induce neuroblast migration from the SVZ niche.